Hearing test results of newborns born from the coronavirus disease 2019 (COVID‐19) infected mothers: A tertiary center experience in Turkey. Issue 1 (16th October 2021) - Yıldız, Gazi; Kurt, Didar; Mat, Emre; Yıldız, Pınar; Başol, Gülfem; Gündogdu, Elif Cansu; Kuru, Betül; Topcu, Bahtisen; Kale, Ahmet
Abstract: Objective: Congenital infections can cause newborn hearing loss. Although vertical transmission of coronavirus disease 2019 (COVID‐19) infection is theoretically possible, this has not been proven yet. To our knowledge, there is no previous report on whether COVID‐19 infection during pregnancy can cause congenital hearing loss. This paper aimed to find an answer to this question. Method: This retrospective, single‐center study was performed between April 2020 and May 2021 at a tertiary care referral center in Turkey. A total of 422 pregnant women who had coronavirus infection during pregnancy were followed and 203 of them gave birth in our institution. Results of hearing screening tests of 199 newborns were assessed retrospectively. Results: Of patients included in the study, 23 (11.6%) had the disease in the first trimester, 62 (31.2%) in the second trimester, and 114 (57.3%) in the third trimester. In the first hearing test performed on newborns, unilateral hearing loss was observed in 21 babies (10.5%). Hearing tests of these newborns were found to be normal in the second test performed 15 days later. Conclusion: Considering the incidence of congenital hearing loss, the absence of hearing loss in our newborn population does not confirm the argument that coronavirus infection does not cause congenital hearing loss. This issue should be evaluated with larger patient series. In addition, it should be kept in mind that hearing loss can occur at later ages as well.